Festival 1981 (Kingston : Jamaica Information Service (JIS), 1981)
Highlights from Festival 1981 - performances in dance, music and spoken word.
Good sound quality.
"Also available as electronic reproduction."
Keywords: Festival 1981 -- Jamaica; Performing arts -- Jamaica